Application, opportunities, and challenges of digital technologies in the decarbonizing shipping industry: a bibliometric analysis - Guangnian Xiao; Lei Pan; Fengbo Lai (Frontiers in Marine Science)
IntroductionAs Digital Industry 4.0 advances, shipping operators are progressively implementing digital technologies for maritime decarbonization efforts.MethodsThis review employs a bibliometric methodology to thoroughly examine and analyze the application of digital technology in decarbonizing shipping from 2005 to 2024. Examining 201 publications from the SCI-EXPANDED and SSCI databases elucidates the present condition, challenges, and prospects of digital technology applications in this domain.ResultsThe review demonstrates the swift expansion of research on digital technologies for decarbonization within the shipping sector via an analysis of annual publication trends. Subsequent journal metrics and collaborative network analysis with VOSviewer identified particularly prolific journals, nations, institutions, and authors. Furthermore, this review delineates the field's principal research clusters and hotspots via keyword co-occurrence analysis, offering direction for future investigations. Ultimately, it examines research gaps in speed optimization, emission prediction, and autonomous ships by integrating keyword co-occurrence analysis with the content of recent publications, and then proposes prospective research options.DiscussionsFuture studies on ship speed optimization could benefit from adopting multi-objective optimization methods, combining more machine-learning techniques with the FCP model, etc. Concerning emission prediction, future research efforts could focus on integrating more diverse external data sources into emission prediction models, adopting emerging technology applications, such as ship-based carbon capture (SBCC), introducing blockchain into smart emission monitoring systems, etc. Future research regarding autonomous ships can further refine optimizing route planning and navigation safety, autonomous ship energy efficiency and emission control, maritime communications and navigation systems, ship electrification, and green design.